Formulasi dan Evaluasi Sediaan Clay Mask Ekstrak Daun Kelengkeng (Dimocarpus longan Lour.) Sebagai Antioksidan Dengan Metode 1,1-Difenil-2-Pikrihidazil (DPPH) - Riza Dwiningrum; Vicko Suswidiantoro; Mida Pratiwi; Vera Tri Anjani (Journal of Innovative and Creativity, 2025)
Clay mask is a topical preparation designed to maintain skin hydration while providing protection against oxidative stress induced by free radicals. Longan leaves (Dimocarpus longan Lour.) are known to contain flavonoid compounds that function as natural antioxidants, making them a potential active ingredient in clay mask formulations. The study purpose was: This study aimed to evaluate the physical quality characteristics and antioxidant activity of clay mask preparations containing longan leaf extract using UV-Vis spectrophotometry. Materials and methods. An experimental method was employed, involving the formulation of three clay mask variants with extract concentrations of F1 (5%), F2 (10%), and F3 (15%). Results: The results demonstrated that all formulations met the physical quality standards. Antioxidant activity varied among the formulas, with F3 showing the highest activity, indicated by an IC₅₀ value of 44.046 ppm, categorized as very strong. Conclusions. This study is expected to serve as a preliminary reference for future research, including the incorporation of fragrance, antibacterial activity testing, and pharmacological evaluation using animal models.